Hepatitis C virus outbreak in a haemodialysis unit: learning from failures. Issue 3 (November 2016) - Senatore, S.; Galli, C.; Conti, A.; Faccini, M.; Cantoni, S.; Ciconali, G.; Mainardi, G.; Lamberti, A.; Dighera, R.; Radice Trolli, F.; Oggioni, C.; Angelini Sironi, L.; et al.
Summary: The investigation of an outbreak of hepatitis C virus in an Italian haemodialysis (HD) centre showed that three patients acquired infection with the same strain, affecting a chronically hepatitis C virus (HCV)-infected patient receiving HD in the same room and during the same shifts. Through our observational analysis many possible modes of transmission were identified, but none could be definitively identified as the route of HCV spread in this small cluster. This outbreak confirms that repeated opportunities for nosocomial HCV transmission may occur among HD patients due to several breaches in the standard precautions for bloodborne infections by healthcare staff.